The The Impact of Women and Board Structure on Corporate Performance: A Study of Indonesian Palm Oil Firms - Alga Aprila Dwi Purwito; Suparmono Suparmono; Ascariena Rafinda; Rasistia Wisandianing Primadineska (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
The primary objective of this study is to examine the impact of women on boards of directors (WOB), boards of directors (BOD), boards of commissioners (BOC), and independent boards of commissioners (BOCI) on company performance. The company's performance encompasses financial performance, assessed by return on assets (ROA), and market performance, evaluated by Tobin's Q. The population in this study consists of companies listed on the Indonesia Stock Exchange, with a sample of 20 companies selected using purposive sampling technique. The observation period is six years (2019-2024). Hypothesis testing with panel data regression. Following the execution of the Chow test, the Hausman test, and the LM test, the optimal model is identified as panel data regression using the Random Effect Model (Tobin's Q) and the Fixed Effect Model (ROA). The research findings indicate that Women on Board, the Board of Directors, the Board of Commissioners, and independent Commissioners do not affect company performance, whether measured by Tobin's Q or ROA. However, for Tobin's Q, the coefficient is negative, and for ROA, only the BOD and Boci have negative coefficients. The research contributes scientifically and can be utilized by subsequent researchers focusing on the issue of women on boards of directors and board of directors' structure.